A Novel Testing Approach for Oxidative Degradation Dependent Incompatibility of Amine Moiety Containing Drugs with PEGs in Solid-State - Blaž Robnik; Katerina Naumoska; Zdenko Časar (MDPI AG, 2020)
Reactive impurities originating from excipients can cause drug stability issues, even at trace amounts. When produced during final dosage form storage, they are especially hard to control, and often, factors inducing their formation remain unidentified. Oxidative degradation dependent formation of formaldehyde and formic acid is responsible for N-methylation and N-formylation of amine-moiety-containing drug substances. A very popular combination of polyethylene glycols and iron oxides, used in more than two-thirds of FDA-approved tablet formulation drugs in 2018, was found to be responsible for increased concentrations of N-methyl impurity in the case of paroxetine hydrochloride. We propose a novel testing approach for early identification of potentially problematic combinations of excipients and drug substances. The polyethylene glycol 6000 degradation mechanism and kinetics in the presence of iron oxides is studied. The generality of the proposed stress test setup in view of the susceptibility of amine-moiety-containing drug substances to N-methylation and N-formylation is evaluated.